Hymns, songs, and fables, for young people - Follen, Eliza Lee Cabot, 1787-1860 (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1851)
As well as hymns and songs in praise of God and nature, this work contains several songs that advocate the benefits of death over slavery and several fables praising the joys of liberty after escaping captivity.